A 1.ª Faculdade de Letras do Porto na «campanha Homem Cristo» : o arauto de uma fatalidade prenunciada - Araújo, Francisco Miguel (História: revista da Faculdade de Letras da Universidade do Porto, 2017)
Over several decades, the plots of “campanha Homem Cristo” (Homem Cristo campaigns’) became a taboo theme in the history of the 1st Faculty of Arts from the University of Porto. All the controversy around three years from press coverage to parliamentary discussions, where use by Francisco Homem Cristo to reveal facts, slanders and scandals with the purpose of discredit the institution and its director Leonardo Coimbra. However, many of its claim, already been denounced before by other critical voices at academic realms, also uncover some inconvenient truths concerning the school’s managing and educational quality. Reaching a more broader perspective besides outdated personal questions, within the aim of deconstructing this «historiographical myth», it will allowed to recognize the importance of this campaign on the suppression of the first attempt of schooling Arts at the U. Porto.